Stroke and pump thrombosis following left ventricular assist device implantation: The impact of the implantation technique - Nozdrzykowski, Michal; Bauer, Jessica-Marie; Schulz, Uwe; Jawad, Khalil; Bireta, Christian; Eifert, Sandra; Sandri, Marcus; Jozwiak-Nozdrzykowska, Joanna; Borger, Michael A.; Saeed, Diyar (Frontiers in Cardiovascular Medicine, 2023)
Objectives Several studies have shown the potential advantage of less-invasive surgery (LIS) for left ventricular assist device (LVAD) implantation. This study aims to determine the impact of LIS on stroke and pump thrombosis events after LVAD implantation. Methods Between January 2015 and March 2021, 335 consecutive patients underwent LVAD implantation using either conventional sternotomy (CS) or the LIS technique. Patient characteristics was prospectively collected. All patients were followed up until October 2021. Logistic multivariate regression and propensity-matched analyses were performed to account for confounding factors. Results A total of 242 patients (F = 32; 13.0%) underwent LVAD implantation with CS and 93 patients (F = 8; 8.6%) with the LIS approach. Propensity matching generated two groups, including 98 patients in the CS group and 67 in the LIS group. Intensive care unit stay for the LIS group patients was significantly shorter than that for the CS group patients [2 (IQR: 2–5) days vs. 4 (IQR: 2–12) days, p < 0.01]. There were no significant differences in the incidence of stroke events (14% in CS vs. 16% in the LIS group; p = 0.6) or in pump thrombosis (6.1% in CS vs. 7.5% in the LIS group; p = 0.8) between the groups. The hospital mortality rate in the matched cohort was significantly lower in the LIS group (7.5% vs. 19%; p = 0.03). However, the 1-year mortality rate showed no significant difference between both groups (24.5% in CS and 17.9% in LIS; p = 0.35). Conclusions The LIS approach for LVAD implantation is a safe procedure with potential advantage in the early postoperative period. However, the LIS approach remains comparable to the sternotomy approach in terms of postoperative stroke, pump thrombosis, and outcome.